Neuroinflammation and M2 microglia: the good, the bad, and the inflamed - Cherry, Jonathan D (BioMed Central, 2014)
The concept of multiple macrophage activation states is not new. However, extending this idea to resident tissue macrophages, like microglia, has gained increased interest in recent years. Unfortunately, the research on peripheral macrophage polarization does not necessarily translate accurately to their central nervous system (CNS) counterparts. Even though pro- and anti-inflammatory cytokines can polarize microglia to distinct activation states, the specific functions of these states is still an area of intense debate. This review examines the multiple possible activation states microglia can be polarized to. This is followed by a detailed description of microglial polarization and the functional relevance of this process in both acute and chronic CNS disease models described in the literature. Particular attention is given to utilizing M2 microglial polarization as a potential therapeutic option in treating diseases.